ProbSeq—A Fragmentation Model for Interpretation of Electrospray Tandem Mass Spectrometry Data. Issue 1 (2004) - Skilling, John; Denny, Richard; Richardson, Keith; Young, Phillip; McKenna, Thérèse; Campuzano, Iain; Ritchie, Mark
Abstract : We describe a probabilistic peptide fragmentation model for use in protein databank searching and de novo sequencing of electrospray tandem mass spectrometry data. A probabilistic framework for tuning of the model using a range of well-characterized samples are introduced. We present preliminary results of our tuning efforts.